Abemaciclib Therapy Using the MonarchE Criteria Results in Large Numbers of Excess Axillary Node Clearances—Time to Pause and Reflect? - Ahari, Daniel; Wilkinson, Mark; Ali, Nisha; Taxiarchi, Vicky P.; Dave, Rajiv V.; Gandhi, Ashu (Cancers, 2024)
The monarchE study added the CDK4/6 inhibitor abemaciclib to the care of women with oestrogen-positive (ER+) breast cancers. Eligibility required meeting monarchE criteria—either >3 positive axillary nodes, or 1–3 positive sentinel nodes (SNB+) with tumour size >50 mm or grade 3 cancers. Women were advised to proceed to completion axillary node clearance (cANC) if size/grade criteria were not fulfilled for >3 positive nodes to be identified. However, cANC is associated with significant morbidity, conflicting with the potential benefits of abemaciclib. We analysed data of 229 consecutive women (2016-2022) with ER+ breast cancer and SNB+ who proceeded to cANC, keeping with contemporary treatment guidelines. We used this cohort to assess numbers that, under national guidance in place currently, would be advised to undergo cANC solely to check eligibility for abemaciclib treatment. Using monarchE criteria, 90 women (39%) would have accessed abemaciclib based on SNB+ and size/grade, without cANC. In total, 139 women would have been advised to proceed to cANC to check eligibility, with only 15/139 (11%) having >3 positive nodes after sentinel node biopsy and cANC. The remaining 124 (89%) would have undergone cANC but remained ineligible for abemaciclib. Size, age, grade, and Ki67 did not predict >3 nodes at cANC. Following cANC, a large majority of women with ER+, <50 mm, and grade 1–2 tumours remain ineligible for abemaciclib yet are subject to significant morbidity including lifelong lymphoedema risk. The monarchE authors state that 15 women need abemaciclib therapy for 1 to clinically benefit. Thus, in our cohort, 139 women undergoing cANC would lead to one woman benefitting.